HIV-1 RNAs whose transcription initiates from the third deoxyguanosine of GGG tract in the 5′ long terminal repeat serve as a dominant genome for efficient provirus DNA formation - Yoshida, Takeshi; Kasuya, Yuho; Yamamoto, Hiroyuki; Kawai, Gota; Hanaki, Ken-ichi; Matano, Tetsuro; Masuda, Takao (Journal of virology, 2024)
Since the promoter for transcribing HIV-1 RNA is unique, all viral elements including genomic RNA and viral proteins have to be generated by the unique transcripts through ingenious mechanisms including RNA splicing and frameshifting during protein translation. Previous studies suggested a new mechanism for diversification of HIV-1 RNA functions by heterogeneous transcriptional initiation site usage; HIV-1 RNAs whose transcription initiates from a certain nucleotide were predominant in virus particles. In this study, we established two methods to analyze heterogenous transcriptional initiation site usage by HIV-1 during viral infection and showed that RNAs beginning with one guanosine (G1-form RNAs), whose transcription initiates from the third deoxyguanosine of the GGG tract in 5′ LTR, were primarily selected as viral genome in infectious particles and thus are used as a template to generate provirus for continuous replication. This study provides insights into the mechanism for diversification of unspliced RNA functions and requisites of lentivirus infectivity.